2002
DOI: 10.1108/14635770210418579
|View full text |Cite
|
Sign up to set email alerts
|

The increasing scope of training and development competency

Abstract: Organizations find it increasingly difficult to stay competitive in today’s global economy. Leaders in the workplace are using benchmarking, competency, competency models, and competency studies to help make human resource decisions, such as hiring, training, and promotions. In training and development (T&D), it is helpful for competencies to focus on knowledge, skills and/or abilities. But neither the field of T&D, nor competency within the field, is static. Reported here is a careful review of literature sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
41
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 4 publications
0
41
0
Order By: Relevance
“…According to Garavan (1997) and Berge et al (2002) training is the planned and systematic modification of behavior through learning events, activities and programs which results in the participants achieving the levels of knowledge, skills, competencies and abilities to carry out their work effectively [7] [8]. A formal training program is an effort by the employer to provide opportunities for the employee to acquire job-related skills, attitudes and knowledge [18].…”
Section: Purpose Process and Outcomes Of Trainingmentioning
confidence: 99%
“…According to Garavan (1997) and Berge et al (2002) training is the planned and systematic modification of behavior through learning events, activities and programs which results in the participants achieving the levels of knowledge, skills, competencies and abilities to carry out their work effectively [7] [8]. A formal training program is an effort by the employer to provide opportunities for the employee to acquire job-related skills, attitudes and knowledge [18].…”
Section: Purpose Process and Outcomes Of Trainingmentioning
confidence: 99%
“…The competency characteristics identified in these previous studies shared the common features of being context-bound and relating to work skills and to workplace learning. Furthermore, some researchers have noted that technological advance may also revolutionize the workplace situation and affect which competencies are to be adopted (Berge, Verneil, Berge, Davis, & Smith, 2002). Also, competency models are valued because they offer a consistent framework for integrating human capital management systems, and they help align employee actions with common strategic organizational goals (Moinat, 2003).…”
mentioning
confidence: 99%
“…This review revealed that that there are many different definitions of business competence, from those that highlight the idea of Knowledge, Skills And Abilities (KSAs), to others that capture personality characteristics such as motives, beliefs and values for further discussion see (Baartman et al, 2007;Berge et al, 2002). Nonetheless, there seems to be a consensus that the term competence encompasses the notion of key skills whilst, at the same time, being broader than such skills.…”
Section: Mislem: Project Methodologymentioning
confidence: 99%
“…Following the literature review, project partners adapted from the literature the following definition of competence, which was later included in the final study questionnaires: "Competencies represent a dynamic combination of knowledge, understanding, skills and abilities" adapted from (Baartman et al, 2007;Belasen and Rufer, 2007;Berge et al, 2002;Gillard and Price, 2005;Nabi, 2003;Palmer et al, 2004;Summers and Summers, 1997).…”
Section: Mislem: Project Methodologymentioning
confidence: 99%